Medical Conference on a Complete Digital Platform in Nepal: A Paperless Experience - Parajuli, Niraj; Karki, Anupama; Kayastha, Bhaskar Mohan Meher (Journal of Nepal Health Research Council, 2020)
Medical conferences are held by different medical societies around the world on a regular basis. The society of Dermatologists, venereologists and leprologists of Nepal organized their 15th annual national conference in a complete digital platform making it the first paperless medical conference in Nepal. This conference initiated the use of digital platform for information dissemination and discouraged the use of paper. The mobile applications built for the conference provided information on the scientific programs and also created an unique identity of each registered delegate with an unique quick response code. The code was very valuable during registration and served as meal coupons too. This conference was our small effort towards creating an eco-friendly medical conference. Keywords: Conference; dermatology; digital; eco-friendly; medical; mobile apps; paperless.